Language and Mental Health: Investigating the Relationship between Linguistic Expression and Psychological Well-being - Tanvir, Fakhrul Abedin; Mitu, Mahabuba Islam (International Journal of Health Sciences, 2024)
Purpose: This study delves into the intricate relationship between language and mental health, exploring how linguistic expression influences psychological well-being. Employing a comprehensive approach, we conducted interviews with 100 individuals spanning diverse backgrounds and mentalities, observing them over a six-month period. Our research utilized both quantitative and qualitative methodologies to provide a nuanced understanding of the subject matter. Methodology: Through our investigation, we uncovered compelling evidence suggesting a significant correlation between language use and psychological well-being. Quantitative analysis revealed consistent patterns indicating that individuals who employed more positive, motivational language exhibited higher levels of psychological well-being compared to those who frequently used abusive or negative words. Furthermore, qualitative data shed light on the intricacies of linguistic expression, highlighting the impact of specific words and phrases on individuals' mental states. Participants reported feeling uplifted and empowered when exposed to motivational language, whereas abusive language often triggered feelings of distress and negativity. Findings: These findings underscore the profound influence of language on mental health, emphasizing the importance of fostering positive communication patterns for overall well-being. By promoting awareness of the power of language and encouraging the use of supportive, uplifting words, interventions aimed at improving mental health outcomes can be developed. Unique contribution to theory, policy and practice: This study contributes valuable insights into the relationship between language and psychological well-being, demonstrating the transformative potential of linguistic expression in shaping mental health outcomes. It underscores the need for further research and the development of targeted interventions to harness the positive impact of language on mental well-being.